DERAJAT INFILTRASI LIMFOSIT PADA PENDERITA KANKER KOLOREKTAL SUB-TIPE ADENOKARSINOMA - Muhammad Sahal Imaduddin; Ika Kustiyah Oktaviyanti; Istiana Istiana (Berkala Kedokteran, 2015)
Cancer is the second leading cause of death which contributes 13% of deaths from a total of 22% of deaths from non-communicable diseases in the world. One contributor to the number of cancer deaths in the world is colorectal cancer. The prognosis of colorectal cancer depend on the stage of cancer at time of diagnosis. However, the prognosis of colorectal cancer can also be determined by looking at the degree of infiltration of lymphocytes in cancer. The purpose of this research is to find out the degree of lymphocytes infiltration in patients with colorectal cancer in Laboratory of Anatomical Pathology Banjarmasin from January to December 2013. The method uses descriptive research by observing the colorectal cancer tissues were obtained from the Laboratory of Pathology Banjarmasin. From a study of 32 samples, found the degree of mild lymphocytic infiltration occurred in 12 patients (37.5%), moderate lymphocytic infiltration occurred in 12 patients (37.5%), and severe lymphocyte infiltration occurred in 8 patients (25%). From this study, found that there are differences in the degree of infiltration of lymphocytes in patients with colorectal cancer. Keywords: Colorectal Cancer, Lymphocyte Infiltration, Prognosis